(untitled) (Al-Mansour Journal, 2022)
The efficiency of the performance of the financial activity of banks is the cornerstone in achieving their goals of survival, growth, continuity and mismanagement of this activity, which may eventually lead to what is known as financial failure, which is described as the alarm bell for future financial changes that may eventually lead to financial failure and the announcement of liquidation. The financial activity also plays an important role in the administrative process, as it contributes an effective role in providing the required information to decision makers, regardless of their administrative levels and the type of decision taken. In addition, it provides information that helps in carrying out various forecasting operations, including forecasting financial failure, which is prepared for assisting banks. In achieving the goal of survival, growth, continuity, and finding appropriate solutions to any financial dilemma that you may face, therefore, the causes of financial decline must be known in order to overcome financial failure. Based on the foregoing, the current research is directed to understanding and analyzing the financial variables that ensure the evaluation of the (Bank of Baghdad) sample of the research and the extent of its exposure to financial failure by knowing and studying the financial situation for several years to predict the extent of its ability to continue providing its services, using models to predict financial failure represented by models (Sherrod) and (Springate).